AN OVERVIEW OF CHARACTERISTICS OF MOBILE AD HOC NETWORKS - Madhu, Vidhiya; S.K.M, Sriee (IJRDO -Journal of Computer Science Engineering, 2017)
Mobile Ad Hoc Networks (MANETs) is agroup of multi hop wireless mobile nodes,dynamic topology and infrastructure lessconnectivity in nature. Constructing aprotected protocol for Mobile Ad HocNetwork is a difficult task. There are severalprotocols planned for secure routing inMANETs, and there is a hybrid routingprotocol and it is a group of both proactiveand reactive routing method in MANETs.The accomplishment of proposed protocol isbased on the clustering technique inRouting. Routing Disorder [RD] attack isthe major issue in MANETs, clustering canprovide a basis for the safe contact between